WRITING AN ANALYTICAL EXPOSITION TEXT THROUGH COOPERATIVE SCRIPT STRATEGY - Nyoman Yuningsih; Novarita Novarita (Universitas PGRI Semarang, 2020)
The purposes of this study was to find out and analyze empirically the effects of cooperative script strategy in enhancing the students’ ability in writing analytical exposition text to the eleventh grade students of SMK N 3 OKU who were taught by using cooperative strategy. The study used experimental design with one group pre-test and post-test. The population of the study were 368 students, there were 12 classes with the 35 sample students, the sample took by using cluster random sampling technique. The data collection method used written test in pre-test and post-test. To analyze the test the researcher used t-test in SPSS 21. First, the writers gave pre-test to the students. The second, the writers taught writing by using cooperative script strategy and the third, they gave post-test to the students to know effectiveness of the strategy which was used. The mean of the pre-test was good (65,20). Meanwhile, the mean of post-test was very good (85,31). It could be seen from the result analysis using paired sample t test that output was 0.000 lower than 0,05. From the score, it can be concluded that null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Based on the result finding from this study, the cooperative script strategy was significantly effective to teach writing an analytical exposition text and the writers recommends the teacher use cooperative script strategy in teaching process and also for the students to apply cooperative script strategy to help the students to conveying their idea and improving their writing ability.